Essential Oils and Pure Volatile Compounds as Potential Drugs in Alzheimer’s Disease Therapy: An Updated Review of the Literature - Maggio, Antonella; Rosselli, Sergio; Bruno, Maurizio (Current Pharmaceutical Design, 2016)
Background: The use of aromatic plants to relief different illness is not a new therapy. Actually aromatic plants have been used for many centuries by different cultures around the world. Pharmacological studies provide scientific support to the traditional use of aromatic medicinal plants and aromatherapy; nevertheless, more clinical trials are required regarding to their effectiveness in order to establish a guidance for their use in routine healthcare. Moreover, modern medicine in studies about olfactory function has attained great achievements and got Nobel Prize in 2004. These new searches have obviously fueled interest in the essential oils and volatile compounds of natural origin. Several reviews on the newly discovered AChEi obtained from plants, fungus and marine organisms have also been published over the last years. The majority of these AChEi belong to the alkaloid group, including indole, isoquinoline, quinolizidine, piperidine and steroidal alkaloids. Results: Probably the interest in the essential oils and volatile compounds will be fueled from the new available scientific data about receptor on olfactory mucosa of nasal cavity. It can receive and distinguish different odor molecules, which produce nerve impulse and transmit into olfactory bulb via olfactory nerves. The nerve cells in the olfactory bulb transmit the signals into hippocampus. Because hippocampus is closely related with learning and memory functions, the volatile compounds can be potential drugs in AD therapies.
Keywords: amyloid-β peptide